Seepage monitoring in embankment dams - Johansson, Sam (KTH, Anläggning och miljö, 1997)
Internal erosion, which is one of the major reasons forembankment dam failure, causes an increased seepage flow due toloss of fines. A seepage measuring system is therefore a vitalpart of an embankment dams monitoring system. Manyexisting seepage monitoring systems are not however sensitiveenough to detect small changes in the seepage flow. Temperatureand resistivity measurements represent two methods for seepagemonitoring in embankment dams. They are able to detect effectscaused by time dependent processes such as internal erosion,where the relative accuracy is more important than the absoluteaccuracy. Temperature can normally be easily measured inexisting standpipes. Resistivity measurements are morecomplicated; they require a computer-based monitoring systemand minor technical installations on the dam. The temperature in an embankment dam depends mainly on thetemperature in the air and the water temperature in theupstream reservoir. These two temperatures vary seasonally andcreate temperature waves propagating through the dam. Theseepage rate, and its change with time, can be evaluated frommeasurements repeated at regular intervals. The sensitivity ofthe method depends mainly on the distance between the dam crestand the measurement point, the size of the dam, the location ofthe standpipes, and the temperature variation in the reservoirat the inflow level. The seepage detection level of the methodis about 1 ml/sm2 for a typical Swedish dam with a height ofabout 30 m. The detection level depends linearly on the damheight. Results from field measurements show that the methodgives reasonable information concerning the condition of thedam. Zones with anomalous seepage rates have been located andseepage flow rates have been quantified. Changes in the seepageflow rate as well as the seepage pathway have also beenobserved. The resistivity of the ground depends mainly on theporosity, saturation and clay content. When reservoir waterseeps through a dam, the properties of the water in thereservoir will also affect the resistivity in the dam. Theresistivity of the reservoir water is temperature dependent,but it is also a function of the total dissolved solids. Boththese parameters vary seasonally and this causes variations inthe dam. The seepage flow can be evaluated from the resistivitydata using methods similar to those employed for seepageevaluation from temperature data. The sensitivity is similar tothat of the temperature method but the resolution and accuracyis lower. Zones with anomalous leakage can be located. Groundpenetrating radar and borehole radar methods are based on themeasurement of material dependent properties. These are lesssensitive to seepage changes than flow dependent parameters.The relatively high accuracy obtained by borehole radarmeasurements compensates however for their lower sensitivity toporosity changes. Borehole radar based on tomographic analysiscan be a valuable method for mapping areas with increased andanomalous porosity formed as a consequence of increased seepageand internal erosion. Key words:embankment dams, internal erosion, seepagemonitoring, temperature, resistivity, ground penetratingradar